A case for no Ks - Haida, Andreas; Trinh, Tue (Proceedings of Sinn und Bedeutung, 2019)
We present a novel observation about modified numerals and discuss how it may pose a problem for the syntactic representation of speaker’s belief, hence the grammatical derivation of ignorance inferences.